Secretion of Cytokines and Chemokines by Innate Immune Cells - Paige Lacy (Frontiers Research Topics, 2015)
The release of cytokines, chemokines, and other immune-modulating mediators released from innate immune cells, including eosinophils, neutrophils, macrophages, dendritic cells, mast cells, and epithelial cells, is an important event in immunity. Cytokine synthesis and transportation occurs through the canonical protein trafficking pathway associated with endoplasmic reticulum and Golgi. How cytokines are released upon their exit from the trans-Golgi network varies enormously between cell types, and in many cells this has not yet been characterized. This issue delves into the plethora of cytokines released by innate immune cells, and where possible, shines light on specific mechanisms that regulate trafficking and release of Golgi-derived vesicles. Each cell type also shows varying degrees of dependency on microtubule organization and actin cytoskeleton remodeling for cytokine secretion. Understanding the mechanisms of cytokine secretion will reveal the inner workings of individual innate immune cell types, and allow identification of critical regulatory steps in cytokine release.